RESTRUCTURING PRE-TRIAL DETENTION IN INDONESIA: THE URGENCY OF JUDICIAL SCRUTINY AND HUMAN RIGHTS-BASED CORRECTIONAL REFORMS - Taufik Tri Prabowo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the shift in the meaning of pre-trial detention in Indonesia from an exceptional measure to a routine practice in the criminal justice system. Aggregate data from the last five years shows that more than 25% of detention facility occupants are pre-trial detainees, many of whom have never been legally tried. This phenomenon has triggered an overcrowding crisis, deteriorating the physical and mental conditions of detainees, and decreasing the quality of basic rights protection in the correctional system. This research uses mixed-methods methods, combining quantitative analysis based on aggregate data on detention, detention growth, and detention center capacity over the past five years, with qualitative analysis of policy documents, regulations, and penitentiary and human rights law literature. Primary data were obtained from national detention authorities, while secondary data were collected from DGC annual reports, government publications, and civil society organization studies and advocacy. Analysis was conducted through descriptive statistics to map trends and patterns of overcrowding, as well as through critical policy review to identify root causes and formulate reform solutions. The main findings highlight the absence of effective judicial scrutiny mechanisms as the root cause of subjectivity and abuse of power in pre-trial detention practices. Dualism in the management of detention facilities between the police, prosecution, and the Ministry of Immigration and Corrections exacerbates fragmentation of oversight, creates legal uncertainty, and weakens institutional accountability. In addition, weak pretrial mechanisms and the lack of alternatives to non-custodial detention further exacerbate the situation, so that pre-trial detention, which should be a last resort, has turned into a habit that jeopardizes the principles of justice, due process of law, and the protection of human rights. The study recommends the establishment of substantive and independent judicial scrutiny mechanisms, harmonization and centralization of detention facility management under the Ministry of Immigration and Corrections, strengthening access to justice and revitalizing habeas corpus, and expanding the use of non-custodial alternatives to detention. These reforms are expected to reorganize Indonesia's pre-trial detention system towards a more just, humane and accountable criminal justice system based on human rights